2019
DOI: 10.1371/journal.pone.0219038
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of carvacrol against resistant rapidly growing mycobacteria in the planktonic and biofilm growth mode

Abstract: Rapidly growing mycobacteria (RGM) are environmental bacteria found worldwide with a propensity to produce skin and soft-tissue infections. Among them, the most clinically relevant species is Mycobacterium abscessus . Multiple resistance to antibiotics and the ability to form biofilm contributes considerably to the treatment failure. The search of novel anti-mycobacterial agents for the control of biofilm growth mode is crucial. The aim of the present study was to evaluate the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Our results show an antimicrobial activity of RSV against resistant H. pylori strains similar to previous studies [ 45 , 46 , 47 , 48 , 49 ]. In particular, Paulo et al [ 28 ] suggested a possible mechanism of RSV action related to the inhibition of H. pylori urease activity, preventing the production of the alkaline environment around bacterial cells, allowing the microorganism to survive the stomach acidic conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Our results show an antimicrobial activity of RSV against resistant H. pylori strains similar to previous studies [ 45 , 46 , 47 , 48 , 49 ]. In particular, Paulo et al [ 28 ] suggested a possible mechanism of RSV action related to the inhibition of H. pylori urease activity, preventing the production of the alkaline environment around bacterial cells, allowing the microorganism to survive the stomach acidic conditions.…”
Section: Discussionsupporting
confidence: 92%
“…Ciprofloxacin, at MIC values, was used as positive control for all detected strains ( Marini et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Body cells and tissues are continuously threatened by the injury caused by free radicals and reactive oxygen species (ROS) which are produced during normal oxygen metabolism or are induced by exogenous damage [122]. Eventually, these excess ROS can produce unadorned oxidative stress to the bacterial cell membrane leads to increased permeability, nucleic acid damage and oxidation of protein and fatty acids in the membrane (Figure 3) [123][124][125]. Unfortunately, these free radicals can attract various inflammatory mediators in the host, contributing to a general inflammatory response and host tissue damage.…”
Section: Inhibition Of Cell Wall Formationmentioning
confidence: 99%
“…These synergistic approaches largely evade toxicity and intolerance of the drug [79]. Previously, various in vitro investigations have been studied and reduce the minimum inhibitory concentration of bioactive compounds with conventional antimycobacterial agents (Table 3) [123][124][125]144,153,181,193,194].…”
Section: Synergistic Action Of Flavonoids With Antimycobacterial Agentsmentioning
confidence: 99%